Strengthening Mental Well-Being Through Islamic Education: A Holistic Framework for Student Development - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This study explores the contribution of Islamic education to strengthening students' mental well-being through a holistic educational approach. Using qualitative library research, the study synthesizes scholarly literature concerning Islamic psychology, educational well-being, character education, and spiritual development. The findings demonstrate that Islamic education contributes significantly to students' psychological resilience by integrating spiritual awareness, emotional regulation, moral development, gratitude, patience, and social responsibility into educational practices. Learning experiences grounded in Qur'anic values encourage students to develop positive coping strategies, emotional intelligence, and meaningful life perspectives. The study proposes a holistic educational framework integrating spiritual, emotional, cognitive, and social dimensions to promote students' overall well-being. The novelty of this study lies in presenting a comprehensive conceptual model that connects Islamic educational philosophy with contemporary mental well-being frameworks while maintaining the centrality of spiritual development